Sodium Channel Blocking Activity and In-vivo Testing of New Phenylimidazole Derivatives - Rivara, Mirko; K. Patel, Manoj; Rapalli, Alberto; Zuliani, Valentina (Letters in Drug Design & Discovery, 2016)
We previously reported the discovery of diphenylimidazoles as potent sodium channel blockers, potentially useful in the treatment of epilepsy. In this work we further explore the structural requirements necessary for the potency of these derivatives with the aim to understand which structural modifications of the original scaffold could be tolerated in order to retain activity. We have synthesized new compounds working on the 2-position of the imidazole ring. First we have introduced a carbonyl spacer, that was subsequently reduced to alcohol. Both carbonyl and alcohol derivatives have been tested for their ability to block NaV1.6 sodium channel subtype in vitro and for their antiepileptic activity in rodent acute seizures models.
Keywords: Sodium channels